COVID-19: REPERCUSSIONS ON THE MENTAL HEALTH OF PROFESSIONALS WORKING IN PRIMARY CARE - Rodrigues Vitorio Pacheco, Dirce (Health and Society, 2023)
Introduction: Even with these measures imposed, to control Covid, health services were overcrowded, saturated and with high demands for professionals. In view of this, through the overload that was placed on health professionals, several consequences emerged, generating a direct impact on the quality of work of the multiprofessional team. Among the main consequences, physical and mental fatigue and the development of mental illnesses such as depression, anxiety, panic reactions and stress emerge. In view of this, the realization of this study is justified by its academic, scientific and social relevance, based on presenting the main disorders triggered by the Covid-19 pandemic in the multiprofessional health team, working in primary care, as well as, its main damages caused. their physical and social well-being. Objective: To identify the main disorders that affect health professionals, working on the front line in the fight against the pandemic. Methodology: An integrative literature review was carried out, whose initial objective was to investigate data that answered the problem in question. The searches took place from a data collection, in the scientific bases: LILACS; SCIELO and MEDLINE. Results and Discussions: Through an analysis of the literature, the main outcomes about the damage caused by covid-19 on the mental health of professionals working in primary care were evidenced. In this context, when discussing mental health, it is important to highlight that the complexity in which the disease reached health services was aggressive and left several victims with Covid sequelae. In addition, it has been shown that mental illness in interdisciplinary teams is probably related to social and economic aspects and job retention. Pre-existing conditions such as comorbidities, depression, anxiety and mood disorders are clinically important indicators that can leverage the prevalence of mental disorders. Conclusion: This integrative review highlighted the importance of incorporating health education, as well as the need to expand and qualify assistance and promotion actions aimed at the mental health of professionals working on the front line in the fight against the pandemic. The results presented show that nurses are more likely to develop mental illnesses. Especially since they are in direct contact with the patient.